An Unusual Cause of Biliary Peritonitis on the Background of Acute Pancreatitis: A Case Report - Symeonidis, Dimitrios; Bompou, Efrosyni; Samara, Athina A.; Kissa, Labrini; Tepetes, Konstantinos (The Surgery Journal, 2022)
Introduction Acute pancreatitis can cause a wide variety of local complications, sometimes pretty unusual. In the present report, we present a rather unusual cause of biliary peritonitis on the background of acute pancreatitis.Case Presentation A 41-year-old female patient with biliary acute pancreatitis and concomitant choledocholithiasis required an urgent laparotomy due to signs of sepsis and peritoneal irritation after a trial of conservative management. During laparotomy, the diagnosis of biliary peritonitis was established. Surprisingly, a residual gallstone obstructing the common bile duct at the level of the ampulla was causing bile to reflux, through the common channel, into the main pancreatic duct and subsequently into a partially ruptured acute pancreatic necrotic collection.Conclusion Dealing with the unexpected is a constant challenge for the surgical team dealing with acute pancreatitis patients. Although deferring surgical intervention during the course of acute pancreatitis, as much as possible, is the ideal strategy, this is not always possible. Deciding the treatment strategy based on the patients' clinical condition represents the most appropriate approach.
Keywords: acute pancreatitis; biliary peritonitis; local complications; necrotic collections